Dominica : Request for Disbursement Under the Rapid Credit Facility: Staff Report and Press Release. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
This paper examines the staff report for Dominica's Request for Disbursement under the Rapid Credit Facility. Dominica has been hit by a number of natural disasters during July-September 2011. Although the impact on growth may be limited owing to the localized nature of the damage, the disasters will have large fiscal and balance of payment costs as the government undertakes the necessary rehabilitation work, including relocation of people from the affected areas. Medium-term prospects remain subdued owing to lack of clear growth drivers, with potential growth estimated at about 2 percent.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet